The role of consumer-brand engagement towards driving brand loyalty: Mediating effect of relationship quality. (1st October 2019) - Adhikari, Kishalay; Panda, Rajeev Kumar
Abstract : Purpose: The present research attempts to empirically examine the influence of consumer-brand engagement, its potent antecedents, and relationship quality towards creating and enhancing brand loyalty of automobile brands in Indian context. Design/methodology/approach: Primary data through survey questionnaires were used to gather empirical data from 443 automobile consumers, out of which 417 samples were included in the final analysis. Structural equation modelling technique was used for assessing the hypothesized direct and indirect relationships among the constructs. Findings: The empirical findings exhibit consumer involvement and brand interactivity contributes positively and significantly towards consumer-brand engagement, while self-brand image congruity does not significantly influence consumer-brand engagement. Further, mediation analysis results show that relationship quality partially mediates the linkage between consumer-brand engagement and brand loyalty. Research limitations/implications: The outcomes of this research may provide novel insights and contribute to the limited body of knowledge regarding consumer-brand engagement. In addition, the findings may assist the automobile brand managers and market strategists to design strategies aimed at developing long-term consumer relationships. Originality/value: This empirical research assesses the mediating effect of relationship quality in the linkage between consumer-brand engagement and brand loyalty for automobile brands, and to the best of our knowledge, has not been attempted by prior researchers in this domain.